Battered wives–measures by the social and medical services. Issue 771 (January 1990) - Bergman, B.; Brismar, B.
Abstract : The social files and medical records of 98 acutely battered wives who attended a surgical emergency department were studied. Although all women had been hospitalized during the decade preceding the present incident, wife battering was documented in the records in only 18%. The majority of the women (73%) were also known to the social services, but battering was documented in less than half of the cases in the social service files. The measures taken by the social services to help the battered women consisted mainly of economic support and psychotherapy. The cooperation between the medical and social services and the police in cases of wife battering was very limited or non-existent. It is concluded that support given to battered women by the formal sources of aid is insufficient. The documentation of the cases is poor, there is a lack of practical measures and the cooperation between the authorities is limited. This study indicates that the social and medical services underestimate the importance of informal help sources like women's groups or shelters which often are the most valued resources by the battered women themselves. With improved cooperation between authorities and between formal and informal sources of aid the battered wives could be helped more effectively.